2008
DOI: 10.1038/bmt.2008.335
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration, health status and quality of life after rhG-CSF-stimulated stem cell collection in healthy donors: a cross-sectional study

Abstract: Mobilized allogeneic PBPC are increasingly used instead of BM for allogeneic stem cell grafting. Although the short-term safety profile of recombinant human (rh)G-CSF seems acceptable, only minimal data on long-term safety are available. We therefore reviewed data on 171 sibling donors (M/F: 98/73) with respect to side effects of rhG-CSF and PBPC collection and impact on quality of life (QoL) and health status. In a cross-sectional study, we investigated the actual QoL and health status of the donors as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
5
26
0
1
Order By: Relevance
“…Fewer donors in our study (40-50%) experienced the side effects of G-CSF administration when compared with reports from other authors (50-90%). These data may be biased due to the subjective nature of the donors' complaints and also differences in the rating of the symptoms [18][19][20]. The frequency of apheresis-related complications was consistent with that previously described [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…Fewer donors in our study (40-50%) experienced the side effects of G-CSF administration when compared with reports from other authors (50-90%). These data may be biased due to the subjective nature of the donors' complaints and also differences in the rating of the symptoms [18][19][20]. The frequency of apheresis-related complications was consistent with that previously described [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…The survey of Halter et al included 1 case of Hodgkin disease; another case has been reported by Leitner et al, both in male PBSC donors who were siblings of patients with hematologic malignancies. 16,34 The sample size investigated in our study is still far too small to allow any conclusion to be drawn. Therefore, although our data provide an interim analysis, they call for a prolonged and thorough follow-up of the increasing number of volunteer donors receiving rhG-CSF for PBSC mobilization.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, this is the lowest frequency reported so far and may be attributed to the young age of our unrelated volunteer donors (median, 34 years) and the use of highly experienced staff. In the study of Leitner et al, 16 central venous access was needed in 2 of 171 (1.1%) related donors. This resembles our own experience in 328 related donors with a median age of 49 years (range, 5-74 years), 4 (1.2%) of whom required a central line.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Large volume bone marrow (BM) harvest is an alternative to G-CSF-induced peripheral blood stem cell collection in patients or donors who are poor mobilizers, in the paediatric setting or in the regenerative medicine, when patients with myocardial infarction are intended to receive stem cells intracardially [1][2][3][4]. Donors and patients are at risk to develop a severe anaemia because collected BM can contain up to 20% of their red cell mass.…”
Section: Introductionmentioning
confidence: 99%